Solvlng Non-Linear First Order Ordinary Differential Equations. - Taremwa, Elias (Kabale University, 2024)
The initial value problem for a first-order system of ordinary differential equations is that much emphasis is put on finding solutions for linear differential equations leaving out nonlinear ones. Many physical applications lead to higher-order systems of ordinary differential equations, but there is a simple reformulation that will convert them into equivalent first-order systems. The main objective of the study was to compare different methods used in solving nonlinear first-order ordinary differential equations